EXPERIENCING URBAN SPACES: ISOVISTS PROPERTIES AND SPATIAL USE OF PLAZAS - BADA, Y.; FARHI, A. (Courrier du Savoir, 2014)
This paper starts from the assumption that a good space is a used space and that people’s behavior, movement and use, is primarily correlated to the potential of both the spatial structure and the visuals fields created by the spatial configuration: visibility. The success is attributable to “…how well the spatial configuration fits real pattern of human behavior” (Hillier 2004). The use of space is governed by two considerations: Its attractiveness, in term movement, how easy for people to move in; as to-movement and through-movement space, and the conduciveness of its visual properties to people’s activities. The correlation between the spatial use and isovists proprieties of space is the focus of this paper that is divided into two parts. The first, a comparative study of four plazas, considering the concept of natural movement about the “accessible destination” and space intelligibility, is carried out to look for the correlation of the number of static people (sitting and standing position) and syntactic and isovist properties of each plaza within the urban layout embedding all of them, the city center district of Biskra. In the second, taking only one plaza, to explore why within it some parts are busy and preferred by people to others; considering only stationary activities of sitting and standing positions. In order to grasp this deeply, believing that a space may have many sub-settings, the plaza has been subdivided into many subspaces to look for links between visibility and spatial use. To achieve this goal the paper relies on overlapping two methods ; behavior mapping, by people counting and spatial use mapping, and space syntax methods initiated by Bill Hillier and visibility graph analysis by using Depthmap, a software developed by Alasdair Turner at UCL.